Perspective models of developing educational activities of Sunday schools - Maxim A. Sannikov (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The paper reveals the theoretical and methodological basis of the activities of Sunday schools in the parishes of the Russian Orthodox Church on the basis of religious and secular educational approaches. The author of the paper offers several models of educational activities and describes the activities of Sunday schools basing on the analysis of philosophical pedagogical literature: Sunday school supplementary education, supplementary Sunday training and pedagogical support for children, currently undergoing experimental testing at the parishes of Izhevsk diocese. It is the first time when the paper gives statistical and archival information about the number and the formation time of parish Sunday schools before the revolution of 1917 in the territory of Udmurtia that used to be a part of Vyatka Province, as well as the statistic information about their modern condition. On the basis of archival and statistical data, the paper gives an analysis of their activities, compares approaches, goals and objectives of the activity. The author explores the dynamic behavior of educational activities of Sunday schools, explains the content of the most advanced models of the educational activities, taking into account the development of modern educational technologies and describing the educational process in the spirit of Orthodox pedagogical culture.